Angular momentum transport in massive stars and natal neutron star rotation rates. Issue 3 (25th July 2019) - Ma, Linhao; Fuller, Jim
Abstract: The internal rotational dynamics of massive stars are poorly understood. If angular momentum (AM) transport between the core and the envelope is inefficient, the large core AM upon core-collapse will produce rapidly rotating neutron stars (NSs). However, observations of low-mass stars suggest an efficient AM transport mechanism is at work, which could drastically reduce NS spin rates. Here, we study the effects of the baroclinic instability and the magnetic Tayler instability in differentially rotating radiative zones. Although the baroclinic instability may occur, the Tayler instability is likely to be more effective for AM transport. We implement Tayler torques as prescribed by Fuller, Piro, and Jermyn into models of massive stars, finding they remove the vast majority of the core's AM as it contracts between the main-sequence and helium-burning phases of evolution. If core AM is conserved during core-collapse, we predict natal NS rotation periods of $P_{\rm NS} ≈ 50\!-\!200 \, {\rm ms}$, suggesting these torques help explain the relatively slow rotation rates of most young NSs, and the rarity of rapidly rotating engine-driven supernovae. Stochastic spin-up via waves just before core-collapse, asymmetric explosions, and various binary evolution scenarios may increase the initial rotation rates of many NSs.